SATELLITE STUDIES OF IONOSPHERIC MANIFESTATIONS OF ACOUSTIC-GRAVITY WAVES - Bespalova, A. V.; Fedorenko, A. K. (Видавничий дім «Академперіодика», 2014)
The response of the ionospheric plasma on the propagation of acoustic-gravity waves (AGW) studied at altitudes of 250 − 350 km using the satellite Dynamics Explorer 2 measurements. Wave perturbations are analyzed according to simultaneously measured data of temperature, concentration and velocity of neutral particles and ions at high and middle latitudes. The following features of ionospheric manifestations of acoustic-gravity waves have been established: 1) relative variations of temperature of neutral particles and ions are roughly the same for these latitudes, except for the regions of auroral ovals; 2) variations in total plasma concentration are antiphase to those in concentration of neutral particles, their relative amplitude being severatimes larger than the amplitude of neutral particles; 3) concentration of molecular ions is in phase with neutral particles;4) vertical velocity of the ions at high latitudes is consistent with that of neutral particles, thus showing their mutual movement along the magnetic field lines. In the high-latitude ionosphere, toseparate the ionospheric manifestations of acoustic-gravity waves from other types of disturbances, the simultaneous analysis of different parameters should be used.Key words:  acoustic-gravity waves, moving ionospheric disturbances, auroral zone, ionosphere, atmosphereManuscript submitted 13.05.2014Radio phys. radio astron. 2014, 19(3): 206-216REFERENCES1. BURMAKA, V.P., TARAN, V. I., andCHERNOGOR, L. F., 2005. Results of the study of wave disturbances in the ionosphere by incoherent scattering. Uspehi sovremennoi radioelectroniki. no. 3, pp. 4–35 (in Russian). 2. LIZUNOV, G. V. and FEDORENKO, A. K., 2006. Atmospheric Gravity Waves Generation by Solar Terminator According to "Atmosphere Explorer-E" Satellite Data. Radio Phys. Radio Astron., vol. 11, no. 1, pp. 49–62 (in Russian). 3. FEDORENKO, A. K., 2009. Determination Characteristics of Atmospheric Gravity Waves in the Polar Regions Using Mass-Spectrometer Satellite Measurements. Radio Phys. Radio Astron., vol. 14, no. 3, pp. 254–265 (in Russian). 4. CARIGNAN, G. R., BLOCK, B. P., MAURER, J. C, HEDIN, A. E., REBER, C. A., and SPENCER, N. W., 1981.The neutral mass Spectrometron Dynamics Explorer. Space Sci. Instrum. vol. 5, pp. 429–441. 5. SPENCER, N. W., WHARTON, L. E., NIEMANN, H. B., HEDIN, A. E., CARIGNAN, G. R., and MAURER, J. C., 1981.The Dynamics Explorer wind and temperature spectrometer. Space Sci. Instrum., vol. 5, pp. 417–428. 6. DUDIS, J. J. and REBER, C. A., 1976. Composition effects in thermospheric gravity waves. Geophys. Res. Lett., vol. 3, No. 12, pp. 727–730. DOI: https://doi.org/10.1029/GL003i012p00727 7. RATCLIFFE, J. A., 1975. An Introduction to the Ionosphere and Magnetosphere. Moscow: Mir Publ. (in Russian). 8. BRYUNELLI, B. E. and NAMGALADZE, A. A., 1988. Physics of the Ionosphere. Moscow: Nauka Publ. (in Russian). 9. LYATSKY,W. B. and MALTSEV, Y. P., 1983. Magnetosphere-Ionosphere Interaction. Moscow: Nauka Publ. (in Russian).